How is IFRS/IAS implemented in China - Wei, Fei (Høgskolen i Bodø, 2007)
Mastergradsoppgave i bedriftsøkonomi - Høgskolen i Bodø, 2007 The thesis investigates how IFRS/IAS is implemented in China. The main idea of the study is to find out the answers of following questions: How has the environment of Chinese accounting changed? What are the reasons for convergence with IFRS/IAS in China? What is the new finding in new accounting standards from perspective of accounting as technology? How can we understand the process of accounting institutionalization in China? Thus, from environmental factors, motivation of reform, implementation process, implementation problems and challenges, and interaction relationship between different actors, the thesis analyzes the China’s new accounting reform. In the global accounting harmonization situation, CAS (China’s accounting standards) convergence with IFRS/IAS is China’s solution to take part in the economic globalization. China government aims at the achievement of compliance between IFRS and China’s new accounting standards (CAS), but differences between CAS and IFRS/IAS still exist. From January 2007, all the listed companies are required to implement the new CAS. Facing the new accounting standards and technique, the lack of professional accountants with international perspective turns to be the “Gap” to the China’s accounting reform.